Electron transport layer material and preparation method and application thereof
By designing an electron transport layer material composed of 9-alkyl-9-phenylfluorenyl, triazine group and cyano-substituted aryl or heteroaryl groups, the problem of low electron mobility of existing materials has been solved. , realizes efficient electron transmission and good thermal stability, and improves the performance of organic electroluminescent devices.
Patent Information
- Application Number
- CN202411682032.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-22
- Publication Date
- 2025-02-14
AI Technical Summary
The electron mobility of the existing electron transport layer materials is lower than that of the hole transport layer, resulting in carrier imbalance, low electron injection efficiency, increasing interface resistance, and reducing the driving voltage and life of the device.
Design an electron transport layer material whose structure is composed of 9-alkyl-9-phenylfluorenyl, triazine group and cyano-substituted aryl or heteroaryl group, and it forms efficient by introducing high electron affinity groups. Electronic transmission channel improves electron mobility and has good thermal stability.
The performance of organic electroluminescent devices with low driving voltage, high luminescence efficiency and long service life is achieved, which significantly improves the electron mobility and thermal stability of the electron transport layer.
Smart Images

Figure CN119431259A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of organic electroluminescence, and in particular relates to an electron transport layer material and a preparation method and application thereof. Background Art
[0002] The electron transport layer plays a vital role in organic electroluminescent devices (OLEDs), and its main function is to facilitate the efficient transfer of electrons from the cathode to the light-emitting layer. The electron transport layer is in contact with the cathode and facilitates the injection of electrons from the cathode into the organic layer. A suitable electron transport layer can reduce the electron injection barrier and improve the electron injection efficiency. The electron transport layer provides an efficient transport path for electrons, allowing electrons to be transferred from the cathode to the light-emitting layer quickly and efficiently, which helps to reduce the loss of electrons during the transport process and improve the overall efficiency of the device. The lowest unoccupied molecular orbital (LUMO) energy level of the electron transport layer needs to match the energy level of the adjacent light-emitting layer and cathode to ensure that electrons can move smoothly from one layer to another. At the interface formed between the electron transport layer and the hole transport layer, electrons and holes combine to form excitons, which then recombine in the light-emitting layer and emit photons.
[0003] Although many materials are currently used as electron transport layer materials, their electron mobility is usually lower than the hole mobility of the hole transport layer, which will lead to carrier imbalance, and low electron mobility may lead to reduced current efficiency because electrons cannot be effectively transferred to the light-emitting layer, thus affecting the generation of light. The energy level matching between the electron transport layer and the cathode is not good, which makes electron injection difficult or the injection efficiency is low, which will increase the interface resistance and reduce the driving voltage of the device, thereby affecting the efficiency and life of the device. Some electron transport layer materials will degrade after long-term operation, especially at high current density. This degradation may be caused by thermal effects, chemical reactions or charge accumulation, which will lead to device performance degradation, such as brightness decay and shortened life.
[0004] Therefore, designing a stable and efficient compound as an electron transport layer material in organic electroluminescent devices to overcome its shortcomings in practical applications is the focus of current research work. Summary of the invention
[0005] In view of the deficiencies in the prior art, the present invention discloses an electron transport layer material and a preparation method and application thereof.
[0006] It should be noted that the electron transport layer material structure disclosed in the present invention is composed of a 9-alkyl-9-phenylfluorenyl group, a triazine group, and an aromatic or heteroaromatic group substituted with a cyano group. These groups have a high electron affinity, forming an efficient electron transport channel, improving the electron mobility of the material, and also having good thermal stability. As an electron transport layer material for an organic electroluminescent device, it achieves low driving voltage, high luminous efficiency, and long service life.
[0007] In order to achieve the above objectives, the first object of the present invention is to provide an electron transport layer material, using the following technical solution:
[0008] An electron transport layer material having a chemical formula I structure:
[0009]
[0010] in,
[0011] R is independently selected from substituted or unsubstituted C1-C6 alkyl;
[0012] Ar1 and Ar2 are each independently selected from hydrogen, substituted or unsubstituted phenyl;
[0013] Ar3 and Ar4 are each independently selected from the following structures:
[0014]
[0015] ; In the formula, R1-R 12 are independently selected from hydrogen, deuterium, substituted or unsubstituted C1-C6 alkyl;
[0016] n1 and n9 are independently selected from integers from 1 to 5;
[0017] n2 and n6 are independently selected from integers from 1 to 9;
[0018] n3, n4, n 11 are independently selected from integers from 1 to 13;
[0019] n5 and n7 are independently selected from integers from 1 to 7;
[0020] n8 is independently selected from an integer from 1 to 8;
[0021] n 10 、n 12 are independently selected from integers from 1 to 11.
[0022] Optionally, at least one of Ar3 and Ar4 is selected from the following groups:
[0023]
[0024] Further, R is independently selected from substituted or unsubstituted methyl, substituted or unsubstituted ethyl, substituted or unsubstituted propyl, substituted or unsubstituted isopropyl, substituted or unsubstituted tert-butyl.
[0025] Furthermore, R1-R 12 independently selected from hydrogen, deuterium, substituted or unsubstituted methyl, substituted or unsubstituted ethyl, substituted or unsubstituted propyl, substituted or unsubstituted isopropyl, substituted or unsubstituted tert-butyl;
[0026] The "substituted" in the above-mentioned substituted or unsubstituted C1-C6 alkyl group refers to deuterium, and the "substituted" in the substituted or unsubstituted benzene ring refers to deuterium, methyl, ethyl, propyl, isopropyl, tert-butyl, tert-pentyl and any combination thereof.
[0027] In the above formula, * represents a connection point.
[0028] Furthermore, the chemical formula I has the following structures of chemical formulas Ia to Ig:
[0029]
[0030] Further, the chemical formula I has any one of the structures of the following compounds 1-184:
[0031]
[0032]
[0033]
[0034]
[0035]
[0036]
[0037]
[0038] The second object of the present invention is to provide a method for preparing the electron transport layer material as described above.
[0039] It should be noted that the material having electron transport function in the present invention, that is, the electron transport layer material, can be prepared by methods known to those skilled in the art. Alternatively, the following reaction process is preferably used for preparation, and the specific operation is as follows:
[0040] (1) Adding raw material A (1.0 eq), raw material B (1.0-1.5 eq) and potassium acetate (2.0-4.0 eq) to a three-necked flask, then adding 1,4-dioxane, passing nitrogen, adding tri(dibenzylideneacetone)dipalladium (0.02-0.10 eq) and X-Phos (0.1-0.2 eq) under nitrogen protection, then heating to 120° C., and reflux reaction for 5-20 hours; detecting the reaction by thin layer chromatography, after the reaction is completed, slightly lowering the temperature, filtering with diatomaceous earth to remove salt and catalyst, then adding water and dichloromethane to the filtrate for separation and extraction, retaining the organic phase and concentrating, and purifying by column chromatography with a mixed solution of dichloromethane and petroleum ether (V:V=1:4-1:10) to obtain intermediate 1;
[0041] (2) Add intermediate 1 (1.0 eq) and raw material C (1.0-1.2 eq) to a three-necked flask, then add a mixed solution of toluene, ethanol and water (V:V:V=3:1:1), pass nitrogen, add tetrakis(triphenylphosphine)palladium (0.02-0.05 eq) and potassium carbonate (2.0-4.0 eq) under nitrogen protection, then heat to 80°C-110°C, and reflux for 6-20 hours; filter using diatomaceous earth to remove salt and catalyst, then add water and dichloromethane to the filtrate for separation and extraction, retain the organic phase, concentrate, and purify by column chromatography using a mixed solution of dichloromethane and petroleum ether (V:V=1:5-1:10) to obtain chemical formula I;
[0042] The specific synthetic route is as follows:
[0043]
[0044] wherein R, Ar1-Ar4 are as defined in Chemical Formula I.
[0045] The third object of the present invention is to provide an application of an electron transport layer material, wherein the electron transport layer material as described above is applied to an organic electroluminescent device.
[0046] Specifically, the organic electroluminescent device comprises an anode, a cathode and an organic layer disposed between the anode and the cathode.
[0047] It should be noted that the organic material layer of the organic electroluminescent device in the present invention can be formed into a single-layer structure or a multilayer structure having two or more organic material layers. For example, the organic electroluminescent device may have a structure including a hole injection layer, a hole transport layer, an electron blocking layer, a light-emitting auxiliary layer, a light-emitting layer, a hole blocking layer, an electron transport layer, an electron injection layer, etc. as organic material layers. However, the structure of the organic electroluminescent device is not limited thereto, and may include a smaller number of organic material layers or a larger number of organic material layers.
[0048] Further, the organic electroluminescent device can be used in an organic electroluminescent device, which includes but is not limited to a flat panel display, a computer monitor, a medical monitor, a television, a billboard, a light for internal or external lighting and / or signaling, a head-up display, a fully transparent or partially transparent display, a flexible display, a laser printer, a telephone, a mobile phone, a tablet, a photo album, a personal digital assistant (PDA), a wearable device, a laptop computer, a digital camera, a video camera, a viewfinder, a microdisplay, a three-dimensional display, a virtual reality or augmented reality display, a vehicle, a video wall including multiple displays tiled together, a theater or venue screen, a light therapy device and a sign.
[0049] Compared with the prior art, the present invention provides an electron transport layer material and a preparation method and application thereof, which have the following excellent effects:
[0050] The electron transport layer material compound disclosed in the invention has good characteristics of electron transport layer material, and the organic electroluminescent device prepared by using the compound has low driving voltage, excellent luminous efficiency and service life.
[0051] Specifically, 1) the 9-alkyl-9-phenylfluorenyl introduced into the electron transport layer material compound disclosed in the present invention has good electron affinity, which enables it to effectively promote the migration of electrons from the cathode to the light-emitting layer or the hole transport layer, and triazine is a strong electron acceptor and also has high electron affinity, which can effectively attract and conduct electrons. The two are directly connected to form an efficient electron transport channel, which significantly improves the electron mobility of the entire material, thereby helping to improve the efficiency of the entire device; and the structure also has good thermal stability, so that it maintains its structural integrity during the evaporation process, thereby effectively improving the life of the device.
[0052] 2) The introduced cyano group is an electron-withdrawing group, a strong electron acceptor with high electron affinity, which means that it can effectively attract and transfer electrons, thereby improving the electron mobility of the electron transport layer. Its presence can also significantly reduce the lowest unoccupied molecular orbital (LUMO) energy level of the molecule. The lower LUMO energy level helps to form a better electron injection and transmission channel, effectively improving the efficiency of the device; and through the strong electron acceptance ability, it promotes charge separation. In the process of photoelectric conversion, it helps to improve the separation efficiency of photogenerated carriers, thereby improving the overall performance of the device. The introduction of cyano groups also increases the rigidity of the molecule, which helps to improve the thermal stability of the material, which is particularly important for the electron transport layer that needs to work at high temperatures, because higher thermal stability can extend the service life of the device. BRIEF DESCRIPTION OF THE DRAWINGS
[0053] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying creative work.
[0054] Figure 1 is the hydrogen nuclear magnetic resonance spectrum of compound 1. DETAILED DESCRIPTION
[0055] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention and the related drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0056] The invention specifically discloses an electron transport layer material and a preparation method and application thereof.
[0057] It should be noted that the numerical values given in the following examples are as accurate as possible, but those skilled in the art understand that due to unavoidable measurement errors and experimental operation problems, each number should be understood as an approximate number rather than an absolutely accurate value.
[0058] The following C-1, D-134 and E-164 are the same substance and are prior art with a CAS number of 73183-34-3.
[0059] The specific embodiments described below are only part of the embodiments of the present application, rather than all the embodiments.
[0060] The features and performance of the present invention will be further described in detail below with reference to the embodiments.
[0061] Example 1
[0062]
[0063] Intermediate 1 is not prior art and is synthesized one step earlier.
[0064] Raw material A-1 (1.1 eq, CAS number: 2921672-89-9) and raw material B-1 (1.0 eq, CAS number: 475156-28-6) were added to a three-necked flask, and then a mixed solution of toluene, ethanol and water (V:V:V = 3:1:1) was added, and nitrogen was passed through. Tetrakis(triphenylphosphine)palladium (0.01 eq) and potassium carbonate (3.0 eq) were added under nitrogen protection, and then the temperature was raised to 95°C, and refluxed for 4 hours; diatomaceous earth was used for filtration to remove salt and catalyst, and water and dichloromethane were added to the filtrate for separation and extraction, the organic phase was retained and concentrated, and a mixed solution of dichloromethane and petroleum ether (V:V = 1:5) was used for purification by column chromatography to obtain intermediate 1 (yield: 78.7%).
[0065] In a three-necked flask, intermediate 1 (1.0 eq), raw material C-1 (1.5 eq) and potassium acetate (2.0 eq) were added, and then 1,4-dioxane was added, and nitrogen was passed through. Tris(dibenzylideneacetone)dipalladium (0.03 eq) and X-Phos (0.1 eq) were added under nitrogen protection, and then the temperature was raised to 120° C., and refluxed for 12 hours; the reaction was detected by thin layer chromatography. After the reaction was completed, the temperature was slightly lowered, and diatomaceous earth was used for filtering to remove salt and catalyst, and water and dichloromethane were added to the filtrate for separation and extraction. The organic phase was retained and concentrated, and a mixed solution of dichloromethane and petroleum ether (V:V=1:4-1:10) was used for purification by column chromatography to obtain intermediate 2 (yield: 72.7%).
[0066] In a three-necked flask, intermediate 2 (1.0 eq) and raw material D-1 (1.0 eq, CAS number: 2260561-71-3) were added, and then a mixed solution of toluene, ethanol and water (V:V:V = 3:1:1) was added, and nitrogen was passed through. Tetrakis(triphenylphosphine)palladium (0.03 eq) and potassium carbonate (3.0 eq) were added under nitrogen protection, and then the temperature was raised to 95°C, and the reaction was refluxed for 15 hours; diatomaceous earth was used for filtration to remove salt and catalyst, and water and dichloromethane were added to the filtrate for separation and extraction, the organic phase was retained and concentrated, and a mixed solution of dichloromethane and petroleum ether (V:V = 1:5) was used to purify by column chromatography to obtain compound 1 (yield: 83.4%).
[0067] The obtained compound 1 was tested and analyzed, and the results were as follows:
[0068] HPLC purity: >99.7%.
[0069] Mass spectrometry test: The model is Waters XEVO TQD mass spectrometer, using ESI source.
[0070] Test value MS (ESI, m / Z): [M+H] + =665.33.
[0071] Elemental Analysis:
[0072] Calculated values: C, 86.72; H, 4.85; N, 8.43;
[0073] The test values are: C, 86.41; H, 5.03; N, 8.62.
[0074] H NMR spectrum: Figure 1 (Compound 1) shown.
[0075] Example 2
[0076]
[0077] The raw material A-39 is the same as the intermediate 2 in Example 1 and is directly used in the next step of synthesis.
[0078] A-39 (1.0 eq) and raw material B-39 (1.0 eq, CAS No.: 2758400-83-6) were added to a three-necked flask, and then a mixed solution of toluene, ethanol and water (V:V:V = 3:1:1) was added, and nitrogen was passed through. Tetrakistriphenylphosphine palladium (0.03 eq) and potassium carbonate (3.0 eq) were added under nitrogen protection, and then the temperature was raised to 95°C, and the reaction was refluxed for 16 hours; diatomaceous earth was used for filtration to remove salt and catalyst, and water and dichloromethane were added to the filtrate for separation and extraction, the organic phase was retained and concentrated, and a mixed solution of dichloromethane and petroleum ether (V:V = 1:5) was used for purification by column chromatography to obtain compound 39 (yield: 84.6%).
[0079] The obtained compound 39 was tested and analyzed, and the results were as follows:
[0080] HPLC purity: >99.8%.
[0081] Mass spectrometry test: The model is Waters XEVO TQD mass spectrometer, using ESI source.
[0082] Test value MS (ESI, m / Z): [M+H] + =679.31.
[0083] Elemental Analysis:
[0084] Calculated values: C, 84.93; H, 4.45; N, 8.25; O, 2.36;
[0085] The test values are: C, 84.65; H, 4.60; N, 8.39; O, 2.52.
[0086] Example 3
[0087]
[0088] Intermediate 1 is not prior art and is synthesized one step earlier.
[0089] Raw material A-134 (1.1 eq, CAS number: 1399482-24-6) and raw material B-134 (1.0 eq, CAS number: 2756733-15-8) were added to a three-necked flask, and then a mixed solution of toluene, ethanol and water (V:V:V = 3:1:1) was added, and nitrogen was passed through. Tetrakis(triphenylphosphine)palladium (0.01 eq) and potassium carbonate (3.0 eq) were added under nitrogen protection, and then the temperature was raised to 95°C, and refluxed for 6 hours; diatomaceous earth was used for filtration to remove salt and catalyst, and water and dichloromethane were added to the filtrate for separation and extraction, the organic phase was retained and concentrated, and intermediate 1 was purified by column chromatography using a mixed solution of dichloromethane and petroleum ether (V:V = 1:6) to obtain intermediate 1 (yield: 76.6%).
[0090] In a three-necked flask, raw material C-134 (1.0 eq, CAS number: 2331184-24-6), raw material D-134 (1.5 eq) and potassium acetate (2.0 eq) were added, and then 1,4-dioxane was added, and nitrogen was passed through. Tris(dibenzylideneacetone)dipalladium (0.03 eq) and X-Phos (0.1 eq) were added under nitrogen protection, and then the temperature was raised to 120° C., and refluxed for 11 hours; the reaction was detected by thin layer chromatography. After the reaction was completed, the temperature was slightly lowered, and diatomaceous earth was used for filtering to remove salt and catalyst, and water and dichloromethane were added to the filtrate for separation and extraction. The organic phase was retained and concentrated, and a mixed solution of dichloromethane and petroleum ether (V:V=1:6) was used for purification by column chromatography to obtain intermediate 2 (yield: 71.8%).
[0091] Intermediate 2 (1.0 eq) and raw intermediate 1 (1.0 eq) were added to a three-necked flask, and then a mixed solution of toluene, ethanol and water (V:V:V=3:1:1) was added, and nitrogen was passed through. Tetrakis(triphenylphosphine)palladium (0.03 eq) and potassium carbonate (3.0 eq) were added under nitrogen protection, and then the temperature was raised to 95°C, and the reaction was refluxed for 18 hours; diatomaceous earth was used for filtration to remove salt and catalyst, and water and dichloromethane were added to the filtrate for separation and extraction, the organic phase was retained and concentrated, and a mixed solution of dichloromethane and petroleum ether (V:V=1:6) was used for purification by column chromatography to obtain compound 134 (yield: 82.8%).
[0092] The obtained compound 134 was tested and analyzed, and the results were as follows:
[0093] HPLC purity: >99.8%.
[0094] Mass spectrometry test: The model is Waters XEVO TQD mass spectrometer, using ESI source.
[0095] Test value MS (ESI, m / Z): [M+H] + =590.30.
[0096] Elemental Analysis:
[0097] Calculated values: C, 83.51; H, 4.62; N, 11.88;
[0098] The test values are: C, 83.22; H, 4.79; N, 12.05.
[0099] Example 4
[0100]
[0101] Intermediate 1 and intermediate 4 are not prior art and are synthesized one step earlier.
[0102] Raw material A-164 (1.1 eq, CAS number: 2530159-39-6) and raw material B-164 (1.0 eq, CAS number: 1011722-07-8) were added to a three-necked flask, and then a mixed solution of toluene, ethanol and water (V:V:V = 3:1:1) was added, and nitrogen was passed through. Tetrakis(triphenylphosphine)palladium (0.01 eq) and potassium carbonate (3.0 eq) were added under nitrogen protection, and then the temperature was raised to 95°C, and refluxed for 6 hours; diatomaceous earth was used for filtration to remove salt and catalyst, and water and dichloromethane were added to the filtrate for separation and extraction, the organic phase was retained and concentrated, and intermediate 1 was purified by column chromatography using a mixed solution of dichloromethane and petroleum ether (V:V = 1:6) to obtain intermediate 1 (yield: 77.1%).
[0103] At -78°C, raw material C-164 (1.2 eq, CAS number: 2791439-58-0) was added to a reaction bottle containing tetrahydrofuran solution, and nitrogen was replaced 3 times. After stirring for 10 minutes, n-butyl lithium (1.2 eq) was slowly added to the reaction bottle and reacted for 2 hours. Raw material D-164 (1.0 eq, CAS number: 19496-13-0) was dissolved in tetrahydrofuran and then slowly dripped into it. After stirring evenly, refrigeration was stopped, and the temperature was raised to room temperature and the reaction was continued for 8 hours. The reaction was detected by thin layer chromatography. After the reaction was completed, water and dichloromethane were added for separation and extraction. The organic phase was retained and concentrated. The intermediate 2 (yield: 73.1%) was purified by column chromatography using a mixed solution of dichloromethane and petroleum ether (V:V=1:3).
[0104] A mixed solution of toluene (5.0 eq) and THF (5.0 eq) was added to a reaction flask, and then intermediate 2 (1.0 eq) was added, and the mixture was stirred at room temperature until dissolved. Subsequently, methanesulfonic acid (5.0 eq) was added to the reaction flask, and the reaction was carried out for 30 min. The reaction was detected by thin layer chromatography. After the reaction was completed, water was added and stirred, extracted, and separated. The aqueous phase was extracted with dichloromethane, the organic phases were combined and concentrated, and a mixed solution of dichloromethane and petroleum ether (V:V=1:6) was used for purification by column chromatography to obtain intermediate 3 (yield: 81.1%).
[0105] In a three-necked flask, intermediate 3 (1.0 eq), raw material E-164 (1.5 eq) and potassium acetate (2.0 eq) were added, and then 1,4-dioxane was added, and nitrogen was passed through. Tris(dibenzylideneacetone)dipalladium (0.03 eq) and X-Phos (0.1 eq) were added under nitrogen protection, and then the temperature was raised to 120° C., and refluxed for 13 hours; the reaction was detected by thin layer chromatography. After the reaction was completed, the temperature was slightly lowered, and diatomaceous earth was used for filtering to remove salt and catalyst, and water and dichloromethane were added to the filtrate for separation and extraction. The organic phase was retained and concentrated, and a mixed solution of dichloromethane and petroleum ether (V:V=1:7) was used to purify by column chromatography to obtain intermediate 4 (yield: 70.6%).
[0106] Intermediate 4 (1.0 eq) and intermediate 1 (1.0 eq) were added to a three-necked flask, and then a mixed solution of toluene, ethanol and water (V:V:V=3:1:1) was added, and nitrogen was passed through. Tetrakis(triphenylphosphine)palladium (0.03 eq) and potassium carbonate (3.0 eq) were added under nitrogen protection, and then the temperature was raised to 95°C, and the reaction was refluxed for 17 hours; diatomaceous earth was used for filtration to remove salt and catalyst, and water and dichloromethane were added to the filtrate for separation and extraction, the organic phase was retained and concentrated, and a mixed solution of dichloromethane and petroleum ether (V:V=1:6) was used for purification by column chromatography to obtain compound 164 (yield: 82.0%).
[0107] The obtained compound 164 was tested and analyzed, and the results were as follows:
[0108] HPLC purity: >99.6%.
[0109] Mass spectrometry test: The model is Waters XEVO TQD mass spectrometer, using ESI source.
[0110] Test value MS (ESI, m / Z): [M+H] + =666.33.
[0111] Elemental Analysis:
[0112] Calculated values: C, 84.79; H, 4.69; N, 10.52;
[0113] The test values are: C, 84.52; H, 4.88; N, 10.70.
[0114] Example 5-57
[0115] The following compounds were synthesized by referring to the preparation methods of Examples 1 to 4 and tested using a Waters XEVOTQD mass spectrometer with low precision. The ESI source was used for testing and the mass spectrometry test values are shown in Table 1 below.
[0116] Table 1 Mass spectrometry test values of Examples 5-57
[0117]
[0118]
[0119] In addition, it should be noted that other compounds of the present invention can be obtained by referring to the preparation methods of the above-mentioned embodiments, so they will not be listed one by one here.
[0120] Device Example 1: Preparation of organic electroluminescent device
[0121] The structure of the prepared OLED device is: ITO anode / HIL / HTL / Prime / EML / HBL / ETL / EIL / cathode / light extraction layer.
[0122] a. ITO anode: the coating thickness is The ITO (indium tin oxide)-Ag-ITO (indium tin oxide) glass substrate was cleaned in distilled water for 3 times, ultrasonically cleaned for 30 minutes, and then repeatedly cleaned with distilled water for 3 times, ultrasonically cleaned for 10 minutes. After washing, it was ultrasonically cleaned with methanol, acetone, and isopropanol in sequence (5 minutes each time), dried, and then transferred to a plasma cleaning machine for washing for 5 minutes. It was then sent to a vapor deposition machine, and the substrate was used as the anode, and other functional layers were deposited thereon in sequence.
[0123] b. HIL (hole injection layer): The hole injection layer materials HT and P-dopant are vacuum evaporated at a deposition rate of 97:3, and the thickness is 10 nm. The chemical formulas thereof are shown below.
[0124] c. HTL (hole transport layer): At a deposition rate of , 130nm of HT was vacuum evaporated on the hole injection layer as a hole transport layer.
[0125] d. Prime (luminous auxiliary layer): At a deposition rate of , 5nm of Prime was vacuum-deposited on the hole transport layer as a light-emitting auxiliary layer.
[0126] e. EML (luminescent layer): At a evaporation rate of , a main material (Host) and a dopant material (Dopant) with a thickness of 30 nm are vacuum evaporated on the light-emitting auxiliary layer as a light-emitting layer. The chemical formulas of Host and Dopant are shown below, where the evaporation rate ratio of Host and Dopant is 98:2.
[0127] f. HBL (hole blocking layer): At a deposition rate of , HB with a thickness of 5.0 nm was vacuum evaporated on the light-emitting layer as a hole blocking layer.
[0128] g. ETL (Electron Transport Layer): At a deposition rate of , compound 1 and Liq with a thickness of 30 nm were vacuum evaporated on the hole blocking layer as an electron transport layer, wherein the deposition rate ratio of compound 1 to Liq was 50:50.
[0129] h. EIL (electron injection layer): A Yb film layer with a thickness of 1.0 nm was vacuum-deposited on the electron transport layer at a deposition rate to form an electron injection layer.
[0130] i. Cathode: Magnesium and silver with a thickness of 13 nm were vacuum evaporated on the electron injection layer at a deposition rate ratio of 1:9 to obtain a cathode.
[0131] j. Light extraction layer: At a deposition rate of , CPL with a thickness of 65 nm was vacuum-deposited on the cathode as a light extraction layer.
[0132] K. Package the vapor-deposited substrate: First, use the glue coating equipment to coat the cleaned cover with UV glue, then move the coated cover to the pressing section, place the vapor-deposited substrate on the upper end of the cover, and finally bond the substrate and cover with the bonding equipment, and complete the light curing of the UV glue at the same time.
[0133]
[0134] Device Example 2-57
[0135] Referring to the method provided in the above device embodiment 1, the corresponding compounds in Table 2 were selected to replace compound 1, and the electron transport layer was evaporated to prepare the corresponding organic electroluminescent devices, which were respectively recorded as device embodiments 2 to 57.
[0136] Device Comparison Examples 1-8
[0137] A comparative device example was prepared according to the method provided in the above device example 1, except that the electron transport layer (compound 1) in the device example 1 was replaced with the existing comparative compound ah, wherein the structural formula of compound ah is as follows:
[0138]
[0139] The driving voltage, BI value and lifespan of the organic electroluminescent devices obtained from the device embodiments 1 to 57 and the device comparative examples 1 to 8 were characterized at a brightness of 1000 (nits). The test results are shown in Table 3 below.
[0140] Table 3 Device test results
[0141]
[0142]
[0143]
[0144]
[0145] Those skilled in the art know that in a blue top-emitting device, the luminous efficiency is greatly affected by chromaticity. Therefore, the influence of chromaticity on efficiency is taken into account, and the ratio of luminous efficiency to CIEy is defined as the BI value, that is, BI = (cd / A) / CIEy.
[0146]
[0147] The comparison compound a and compounds 103, 119, and 139 are parallel comparative examples, and the difference between them is that the triazine in compound a is connected to a benzene ring, while the corresponding positions of the compounds 103, 119, and 139 of the present invention are connected to a cyano-substituted benzene ring, a cyano-substituted pyridine ring, and a phenylcyanopyridyl group (cyano and phenyl are simultaneously substituted on the pyridyl group). It can be seen from the experimental data that compared with the comparison compounds, the device efficiencies of the compounds 103, 119, and 139 of the present invention are increased by 4.69%, 5.26%, and 8.03%, respectively, and the lifespans are increased by 12.5%, 14.4%, and 16.1%, respectively. It can be seen that the device performance of the cyano-containing compound is better, especially under the action of the phenylcyanopyridyl group, because the two electron-withdrawing groups of cyano and pyridyl make the entire molecule have a higher electron affinity, thereby promoting the efficient transmission of electrons from the cathode to the light-emitting layer, and effectively improving the efficiency of the device. The phenyl and pyridine groups can enhance the overall rigidity of the material, which helps improve the stability of the material under high temperature conditions and can effectively extend the service life of the device.
[0148]
[0149] Comparative compound c is a compound in patent CN116655611A previously studied by the applicant, and is a comparative example with compound 81. The difference between them is that: compound 81 of the present invention has a methyl group and a phenyl group at the 9th position of fluorene; comparative compound c has a methyl group and a dibenzofuran group at the 9th position of fluorene. Dibenzofuran has strong rigidity, and the increase of evaporation temperature reduces its stability, thereby shortening the life of the device. According to the data, the device life of compound 81 of the present invention is improved by 5.94% compared with that of comparative compound c.
[0150]
[0151] Comparative compounds e, f and compound 95 are parallel comparative examples, the difference between them is that: the corresponding position of compound 95 of the present invention is connected to 9-methyl-9-phenylfluorenyl, this structure has a higher electron affinity, thereby improving the electron mobility, and the presence of methyl can further optimize the interaction between molecules, thereby improving the electron transfer efficiency. In addition, the structure has good thermal stability, so that it maintains its structural integrity during the evaporation process, thereby effectively improving the luminous efficiency and life of the device; while in the comparative compound e, the triazine side is connected to 9,9-diphenylfluorenyl, the presence of which will introduce more steric hindrance, affecting the electron transfer efficiency, thereby affecting the device efficiency, and the two phenyl groups do not play a role in extending the conjugated system, but increase the molecular weight, making the evaporation temperature higher, causing material instability, and affecting the life of the device; in the comparative compound f, the triazine side is connected to spirobifluorenyl, and its electron mobility is lower than that of 9-methyl-9-phenylfluorenyl.
[0152]
[0153] The comparative compounds g and h are compounds in the patent CN117447414A previously studied by the applicant, and are parallel comparative examples with compounds 163 and 173, respectively. The difference between them is that: there is a phenylene group between the triazine group and the 9-methyl-9-phenylfluorenyl group in the comparative compounds g and h. The introduction of the phenylene group may increase the energy barrier within the molecule, affect the rapid transmission of electrons, and slightly weaken the direct electronic interaction between the two groups. In the compounds 163 and 173 of the present invention, the triazine group and the 9-methyl-9-phenylfluorenyl group are directly connected by a chemical bond. The direct connection between the triazine and the 9-methyl-9-phenylfluorenyl group can reduce the energy barrier within the molecule and form a more continuous π-conjugated system, thereby improving the electron transmission efficiency, and promoting the electronic interaction between the two, making it easier for the charge to be transferred from one part to another. In addition, the directly connected structure is more likely to form a tightly packed material structure, which is beneficial to reducing defects.
[0154] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. An electron transport layer material, characterized in that: The general structural formula of the electron transport layer material is shown in Chemical Formula I: in, R is independently selected from substituted or unsubstituted C1-C6 alkyl; Ar1 and Ar2 are each independently selected from hydrogen, substituted or unsubstituted phenyl; Ar3 and Ar4 are each independently selected from the following structures: ; In the formula, R1-R 12 are independently selected from hydrogen, deuterium, substituted or unsubstituted C1-C6 alkyl; n1 and n9 are independently selected from integers from 1 to 5; n2 and n6 are independently selected from integers from 1 to 9; n3, n4, n 11 are independently selected from integers from 1 to 13; n5 and n7 are independently selected from integers from 1 to 7; n8 is an integer selected from 1 to 8; n 10 、n 12 are independently selected from integers from 1 to 11.
2. The electron transport layer material according to claim 1, characterized in that At least one of Ar3 and Ar4 is selected from the following groups: Among them, * indicates a connection point.
3. The electron transport layer material according to claim 2, characterized in that: R is independently selected from substituted or unsubstituted methyl, substituted or unsubstituted ethyl, substituted or unsubstituted propyl, substituted or unsubstituted isopropyl, substituted or unsubstituted tert-butyl.
4. The electron transport layer material according to claim 2, characterized in that R1-R 12 are independently selected from hydrogen, deuterium, substituted or unsubstituted methyl, substituted or unsubstituted ethyl, substituted or unsubstituted propyl, substituted or unsubstituted isopropyl, and substituted or unsubstituted tert-butyl.
5. The electron transport layer material according to claim 1, characterized in that The substituent represented by "substituted" in the substituted or unsubstituted C1-C6 alkyl group is deuterium, and the substituent represented by "substituted" in the substituted or unsubstituted benzene ring is deuterium, methyl, ethyl, propyl, isopropyl, tert-butyl, tert-pentyl and any combination thereof.
6. The electron transport layer material according to claim 1, characterized in that Chemical formula I has the following structures of chemical formulas Ia to Ig:
7. The electron transport layer material according to claim 1, characterized in that The structure of the electron transport layer material is selected from any one of the following compounds 1-184:
8. A method for preparing an electron transport layer material as claimed in claim 1, characterized in that: The method specifically comprises the following steps: (1) Adding raw material A (1.0 eq), raw material B (1.0-1.5 eq) and potassium acetate (2.0-4.0 eq) to a three-necked flask, then adding 1,4-dioxane, passing nitrogen, adding tri(dibenzylideneacetone)dipalladium (0.02-0.10 eq) and X-Phos (0.1-0.2 eq) under nitrogen protection, then heating to 120° C., and reflux reaction for 5-20 hours; detecting the reaction by thin layer chromatography, cooling after the reaction, filtering with diatomaceous earth to remove salt and catalyst, then adding water and dichloromethane to the filtrate for separation and extraction, retaining the organic phase for concentration, and purifying by column chromatography with a mixed solution of dichloromethane and petroleum ether (V:V=1:4-1:10) to obtain intermediate 1; (2) Add intermediate 1 (1.0 eq) and raw material C (1.0-1.2 eq) to a three-necked flask, then add a mixed solution of toluene, ethanol and water (V:V:V=3:1:1), pass nitrogen, add tetrakis(triphenylphosphine)palladium (0.02-0.05 eq) and potassium carbonate (2.0-4.0 eq) under nitrogen protection, then heat to 80°C-110°C, and reflux for 6-20 hours; filter using diatomaceous earth to remove salt and catalyst, then add water and dichloromethane to the filtrate for separation and extraction, retain the organic phase, concentrate, and purify by column chromatography using a mixed solution of dichloromethane and petroleum ether (V:V=1:5-1:10) to obtain chemical formula I; The specific synthetic route is as follows: wherein R, Ar1-Ar4 are as defined in Chemical Formula I.
9. An application of an electron transport layer material, characterized in that: The electron transport layer material according to any one of claims 1 to 7 is applied to an organic electroluminescent device.
10. The use according to claim 9, characterized in that: The organic electroluminescent device comprises an organic layer; the organic layer comprises the electron transport layer material according to any one of claims 1 to 7.
Citation Information
Cited By
Material with electron transmission function, organic electroluminescent device and application
CN121517401A
Electron transport layer material, preparation method thereof and organic electroluminescent device
CN121673238A
An electron transport layer material, a preparation method thereof and an organic electroluminescent device
CN121673238B